Soccer, politics and the American public: still 'exceptional'?. (16th April 2017) - Collet, Christian
Abstract : In 1988, Andrei Markovits first published the argument that soccer in the United States encounters an 'exceptional' experience because America's 'hegemonic sports culture' has 'crowded out' the sport by virtue of historically determined factors, including popular acceptance. Twenty years after USA '94, it seems appropriate to revisit this idea. In this paper, I utilize survey data from multiple sources to make three arguments. First, interest in soccer among the public has been generally stable over time; second, relative to other countries, American fans are not discernibly exceptional; third, what discerns fans are characteristics that appear to be a function of the sport's diversity. This makes the ongoing 'exceptional' characterization ironic, as the binary continues to serve those who deride soccer as 'un-American'. While Markovits has identified a critical period in soccer's past, moving beyond the deterministic exceptionalist model is imperative for future research on the American game.